2002
DOI: 10.1103/physrevlett.88.077402
|View full text |Cite
|
Sign up to set email alerts
|

Drastic Reduction of Plasmon Damping in Gold Nanorods

Abstract: The dephasing of particle plasmons is investigated using light-scattering spectroscopy on individual gold nanoparticles. We find a drastic reduction of the plasmon dephasing rate in nanorods as compared to small nanospheres due to a suppression of interband damping. The rods studied here also show very little radiation damping, due to their small volumes. These findings imply large local-field enhancement factors and relatively high light-scattering efficiencies, making metal nanorods extremely interesting for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

108
1,949
5
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,662 publications
(2,071 citation statements)
references
References 21 publications
108
1,949
5
9
Order By: Relevance
“…A large number of theoretical and experimental studies were dedicated to the understanding of PP physics and revealed fascinating properties. [1][2][3][4] For example, PPs in gold particles are linked to broad band photoluminescence 2 and strong local field enhancement, making these nanostructures promising candidates for a variety of different applications. 4 In addition, the high biocompatibility of gold nanoparticles has stimulated their widespread use in the biosciences within the last few years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of theoretical and experimental studies were dedicated to the understanding of PP physics and revealed fascinating properties. [1][2][3][4] For example, PPs in gold particles are linked to broad band photoluminescence 2 and strong local field enhancement, making these nanostructures promising candidates for a variety of different applications. 4 In addition, the high biocompatibility of gold nanoparticles has stimulated their widespread use in the biosciences within the last few years.…”
mentioning
confidence: 99%
“…[1][2][3][4] For example, PPs in gold particles are linked to broad band photoluminescence 2 and strong local field enhancement, making these nanostructures promising candidates for a variety of different applications. 4 In addition, the high biocompatibility of gold nanoparticles has stimulated their widespread use in the biosciences within the last few years. [5][6][7][8][9][10] Gold particles were used as intramolecular distance rulers, 5 as non bleaching sensors, 6 and as labels for multiphoton microscopy.…”
mentioning
confidence: 99%
“…The bandwidth, or full width half maximum (FWHM) of the absorption peak is inversely proportional to the coherence time, or period that the oscillating electrons stay in-phase before damping [14,18,19]. The effective radiative damping of a dipolar plasmon will be proportional to the nanoparticle volume where smaller nanoparticles will have intrinsic, or thermoelastic, damping as their dominant decay mechanism [9,20].…”
Section: Localized Surface Plasmon Resonance (Lspr) and Mie Theorymentioning
confidence: 99%
“…The scattering contribution can then be calculated by subtracting the absorption coefficient from the total extinction value. Here the real part of the dielectric constant determines the position of the wavelength while the bandwidth, or time spent dephasing, is determined by the imaginary component [18,[30][31][32][33]. In general, for smaller nanoparticles, <40 nm, the optical extinction is dominated by absorption whereas scattering contributions increase as the diameter of the nanoparticle grows [21,33,34].…”
Section: Localized Surface Plasmon Resonance (Lspr) and Mie Theorymentioning
confidence: 99%
“…Such interaction results in an enhancement of electromagnetic field as well as maximum scattering at a resonant wavelength for a metallic nanostructure, which can be explained by a radiative theory 4, 5. The integration of nanoplasmonics has been demonstrated recently with stretchable, flexible, or biocompatible substrates in order to enable new functionalities for low cost, disposable, and wearable biosensors 6, 7.…”
Section: Introductionmentioning
confidence: 99%